Non-invasive Adenocarcinoma of the Vermiform Appendix: Incidence and Report of Four Cases among 512 Appendectomies - Terada, Tadashi (Gastroenterology Res, 2009)
Tumors of the vermiform appendix are relatively rare. More than 50% of appendiceal tumors are carcinoid tumors. The author reviewed 512 consecutive pathological specimens of appendectomies in last ten years in our pathology laboratory in search for appendiceal tumors. As the results, 4 cases (incidence: 0.8%) of non-invasive adenocarcinoma were found. No other tumors including carcinoid tumors were recognized. The age of the 4 patients with adenocarcinoma was 48, 39, 84 and 86 years, respectively. Male to female ratio was 3:1. The clinical diagnoses were acute appendicitis in 2 cases and suspected malignancy in 2 cases. The post-operative outcome was good without metastasis, recurrence, and pseudomyxoma peritonei. Pathologically, all the 4 tumors were non-invasive adenocarcinomas: 2 cases were flat type adenocarcinoma, 1 case was papillary adenocarcinoma, and 1 case was mucinous adenocarcinoma. Immunohistochemically, expression of p53 protein was observed in all the 4 cases, and Ki-67 labeling ranged from 40% to 90%. The results suggest that incidence of appendiceal adenocarcinoma was 0.8% of all appendectomies, and that non-invasive adenocarcinoma of the appendix shows variable morphologies, and that postoperative clinical outcome of non-invasive appendiceal tumor is good.